Dyslexia: unknown, when not, ignored (Journal of Parents and Teachers, 2012)
The author of this article talks about dyslexia explaining the problems that arise in the students. He also states that is necessary an educative intervention in primary education for students with dyslexia so that they can grow as human being in every single context of life.
Keywords: Dyslexia; primary education; educative intervention; learning process.